Study of the Fillers Influence on Mechanical Properties of Polyamide by Using of AFM - Bakošová, Dana (Manufacturing Technology Journal, 2018)
The works deals with a study of fillers influence on chosen mechanical properties of polyamide and the given influence was investigated by using of atomic force microscopy (AFM). Atomic force microscope NT-206 in a complex with control and image processing software is intended for measurement and analysis of surface microrelief and submicrorelief, objects of the micrometer and nanometer range with high resolution. Using AFM it is possible to scan spectroscopic curves that show dependence of composite action force of the probe and surface of the sample on distance between them - they are curves of approach /moving off. In presented measurements by using of spectroscopic curves, the homogeneity and ratio of Young's modulus for polyamide samples were evaluated. For each sample, the curve was created by using of five different places - points. We employed the general approximation and Snedonn's formula for analysis of data and calculation of Young's modulus off complete rake curve. The Sneddon's model gives the relationship between load gradient dP/dh and Young's modulus E.
Keywords: Polyamide; AFM; Spectroscopic curve; Sneddon's model; Young's modulus